(untitled) (Journal of Imam Al-Kadhim College, 2024)
Poverty is one of the prominent challenges facing developing countries, adversely affecting economies and societies. The role of foreign labor exacerbates poverty rates in these countries, as their presence intensifies competition for jobs with local workers, leading to wage reduction, increased unemployment, and consequently higher poverty rates. Additionally, foreign labor may diminish local job opportunities and distort fair wealth distribution, exacerbating economic and social inequality. Furthermore, foreign labor may sometimes be exploited in illicit activities such as organized crime, exacerbating social and security issues. There is an urgent need to adopt effective policies to manage foreign labor and ensure that the national economy benefits from their expertise without negatively impacting local workers and communities. These policies should focus on providing employment opportunities for local labor, ensuring equal opportunities in the job market, and enhancing social and legal protection for foreign workers. Moreover, these policies should include measures to improve the economic and social conditions of the most impoverished groups, aiming to achieve sustainable development and social justice in developing countries like Iraq.